Suitability, success and sinks: how do predictions of nesting distributions relate to fitness parameters in high arctic waders?. Issue 12 (28th June 2013) - Pellissier, Loïc; Meltofte, Hans; Hansen, Jannik; Schmidt, Niels M.; Tamstorf, Mikkel P.; Maiorano, Luigi; Aastrup, Peter; Olsen, Jeppe; Guisan, Antoine; Wisz, Mary S.
Abstract: Aim: Although habitat suitability maps derived from species distribution models (SDMs) are often assumed to highlight locations that can sustain healthy populations over time, the relationship between suitability scores and fitness parameters has rarely been tested thoroughly. Location: Zackenberg Valley, north‐east Greenland. Methods: Using 14 years of data (1997–2010) representing three wader species (dunlin Calidris alpina, sanderling Calidris alba and ruddy turnstone Arenaria interpres ), we tested the relationships between modelled suitability and fitness parameters at nesting locations. Results: Among the three species examined, only the ruddy turnstone exhibited significant relationships between suitability and nest success, but over time rather than space. During years with extensive snow cover in the landscape, the nesting sites of ruddy turnstone occurred in different habitats than were typically used across years. Moreover, in years with extensive snow cover, the ruddy turnstone initiated nests later and suffered from higher egg predation rates. Main conclusion: Our results suggest that SDMs derived from species occurrences that include years of low reproductive success may over‐estimate the potential suitable habitat in the landscape. Whenever possible, variation in reproductive success should be considered when building models to inform species' response to environmental change.